Contracting for Artificial Intelligence - Sako, M (Association for Computing Machinery, 2023)
"Modern economies are held together by innumerable contracts," which underpin high-performing and trusted trading relationships.a While data scientists, with contracting professionals, are busy developing artificial intelligence (AI) tools for contract management, not enough attention is paid to resolving an important issue, namely new challenges posed when contracting for the use of AI tools and data. This column argues such consideration is essential for enhancing the competitive advantage of providers and users of AI tools and would contribute to public good. I begin by discussing efforts made to apply AI and machine learning (ML) for contract management and then shift attention to challenges of contracting for AI by addressing a question central to this column: What characteristics of AI/ML make it distinctively difficult to contract? And what solutions exist to deal with these challenges?